Learning Objects in Online Education: A Systemic Approach - Vieyra, Gerardo Quiroz; González, Luis Fernando Muñoz (European Journal of Education (EJE), 2020)
In the construction of learning objects, as digital instructional material that is delivered to students, the level of learning to which they are directed must be considered first of all, according to the Bloom taxonomy or any other that is used, applicable to the e-learning, taking advantage of the digital resources that are currently available, multimedia for creation, digital repositories for storage and internet for access. Learning objects are built with pedagogical and technological elements that follow a process in themselves, subject to an educational model, instructional design, curriculum design and learning objectives as precedents, with stages very similar to those of design, construction and operation of an information system. Given their nature of digital entities, learning capsules that contain information and knowledge, the Data Quality Model of the ISO / IEC 25012: 2008 standard is also applicable, which guarantees the quality of the content and their access and availability. The creation of learning objects must also obey an educational strategy and be considered holistically in the e-learning system, that is, use a systemic approach throughout the teaching-learning process, including learning objects, considering harmonization, performance and quality in all its stages.